IODP Scientific Prospectus 2005
DOI: 10.2204/iodp.sp.311.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cascadia margin gas hydrates

Abstract: Expedition 311 Scientists PUBLISHER'S NOTESMaterial in this publication may be copied without restraint for library, abstract service, educational, or personal research purposes; however, this source should be appropriately acknowledged. Katerina Petronotis Yeoperson Martin Rothfuss Pressure Coring Engineer Philip RumfordCuratorial Specialist Derryl Schroeder Drilling Engineer Michael StormsOperations Superintendent Scott TowesMarine Mammal Observer (7-18 October) Floris TuynderPressure Coring Engineer 7 Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…However, shallow (Figure 2). At the same time, like other gas hydrate locations, the increasing ratios of Mg 2+ /Ca 2+ and Sr 2+ /Ca 2+ manifest calcite precipitation is the most important process in shallow sediments [52,53] (Figure 4). SMI depths, relative high sulfate flux and high I flux, and obvious carbonate precipitation within shallow sediments in the Shenhu area indicate intensive microorganism activities in shallow sediments and fluids upwelling from depths.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, shallow (Figure 2). At the same time, like other gas hydrate locations, the increasing ratios of Mg 2+ /Ca 2+ and Sr 2+ /Ca 2+ manifest calcite precipitation is the most important process in shallow sediments [52,53] (Figure 4). SMI depths, relative high sulfate flux and high I flux, and obvious carbonate precipitation within shallow sediments in the Shenhu area indicate intensive microorganism activities in shallow sediments and fluids upwelling from depths.…”
Section: Discussionmentioning
confidence: 80%
“…At the same time, like other gas hydrate locations, the increasing ratios of Mg 2+ /Ca 2+ and Sr 2+ /Ca 2+ manifest calcite precipitation is the most important process in shallow sediments [52,53] (Figure 4). …”
Section: Precipitation Of Authigenic Carbonatesmentioning
confidence: 80%
See 1 more Smart Citation
“…The purpose of this newly installed system is to monitor the gas‐hydrate deposits known to be present in the area (see Mir 2011). Collett et al . (2005) and Riedel et al .…”
Section: Introductionmentioning
confidence: 99%
“…Site U1329 (proposed Site CAS-05D; Collett et al, 2005) is at the easternmost end of the southwest-northeast-trending, marginperpendicular transect of sites drilled during Integrated Ocean Drilling Program (IODP) Expedition 311 and is located closest to shore (65 km) at a water depth of 946 m. Newly acquired bathymetry data showed that this site is located in an area characterized by multiple canyons of various sizes where water depth decreases rapidly from 500 to 1300 m over a distance of only 7.5 km with an average slope of 6° (Figs. F3 and F4 in the "Expedition 311 summary" chapter).…”
Section: Background and Objectivesmentioning
confidence: 99%